The dangers of Utopia - Hufford, Larry (Revista Espaço Acadêmico)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Utopia can have an uplifting and a dark side, but usually the dark side ends up trumping the initial idealism. The reason for this is that utopians inevitably adopt a messianic image of the world. The three messianic revolutions in history—the American, French and Bolshevik—were led by men who thought their ideas were universal. This essay examines the writings of French existentialist Albert Camus, who argues that there are no transcendental values, at the same time he does not accept nihilism. Camus makes a distinction between a rebel and a revolutionary, and concludes that a rebellion will try to end the specific oppression, whereas the revolution will try to create a “new man,” with common values throughout the world.